Light spectra blocking films reduce numbers of western flower thrips, Frankliniella occidentalis (Thysanoptera: Thripidae) in strawberry, Fragaria x ananassa. (9th July 2022) - Fountain, Michelle T.; Delgado, Alvaro; Deakin, Greg; Davis, Frederick; Hemer, Sebastian
Abstract: Frankliniella occidentalis is a pest of horticultural crops, including commercial strawberry ( Fragaria x ananassa ). Control is challenging because certain populations are resistant to insecticides and, in strawberry, now relies on the application of biocontrols. However, this approach is not always successful if F. occidentalis populations overwhelm biocontrols. We investigated whether targeted spectral modifications to cladding materials could reduce numbers of F. occidentalis, in strawberry flowers. Five UV‐attenuating plastic‐film materials were tested in three, 6‐week, semi‐field tunnel experiments containing strawberry plants. F. occidentalis were introduced into tunnels from a laboratory culture and subsequent numbers that developed in strawberry flowers were recorded. Limiting UV‐A radiation to the crop significantly reduced the numbers of adult and larval F. occidentalis in strawberry flowers. The numbers of adult (and larvae) in flowers were reduced by 42 (47)%, 54 (41)%, 70 (73)%, and 82 (73)% in UV350, UV370, UV400, and UV430‐attenuating films, respectively, compared with the UVopen (control) film. However, no damage to strawberry fruits was observed regardless of the film treatment. Incorporating UV‐attenuating films as tunnel cladding can suppress F. occidentalis numbers in strawberry. Reducing populations of F. occidentalis in crops is likely to enable the more successful use of other non‐chemical control strategies. Abstract : Frankliniella occidentalis populations are halved in strawberry crops covered with UV‐attenuating tunnel claddings Frankliniella occidentalis populations are halved in strawberry crops covered with UV‐attenuating tunnel claddings UV‐attenuating films have the potential to reduce the application of chemical pesticides UV‐attenuatting films can reduce thrips numbers in strawberry crops